Inflation Perceptions and Expectations in Sweden - Are Media Reports the `Missing Link'? - Lena Dräger (Hamburg University, Department Economics and Politics, 2011)
Using quantitative survey data from the Swedish Consumer Tendency Survey as well as a unique data set on media reports about inflation, we analyze the formation process of inflation perceptions and expectations as well as interrelations between the variables. Throughout the analysis, the role of media reports about inflation is emphasized and results for the low inflation period January 1998 to December 2007 are compared to those including the high inflation year 2008. Rejecting rationality, we find that perceptions, but not expectations, are affected asymmetrically by news, where media effects are generally stronger in times of high and volatile inflation. For the low inflation sample period, inflation expectations are more affected by shocks to perceptions than vice versa, but Granger causality runs from expectations to perceptions. Including more volatile inflation, we find more feed-back between the variables and a strong media effect especially on perceptions.
Keywords: C32; E31; E37; 330; Inflation expectations; inflation perceptions; media reports